An adolescent with newly diagnosed Wilson disease having underlying type 1 diabetes: A previously unreported combination - Neeraj Kumar; Sunisha Jakhar; Dinkar Yadav; Neha Yadav; Kapil Bhalla (Journal of Family Medicine and Primary Care)
Wilson’s disease is a copper deposition disease; involving the brain, liver, and eyes with onset commonly in adolescent age group. The onset of symptoms typically occurs around 12–15 years of age. The usual manifestations are hepatic (40% of the cases), neurological (35%) or psychiatric (10%). It has been seen associated with various endocrinopathies like hypothyroidism and hypoparathyroidism but its association with type 1 diabetes mellitus very rare. To the best of our knowledge, no case has been reported about association of type 1 diabetes mellitus with Wilson disease. Here we report a case of 14-year-old male patient, who was diagnosed with type 1 diabetes mellitus one year back, now presented with neurological symptoms. On further investigations patient was found to have Wilson’s disease.